Symmetry Conditions for Market Demand Functions - Diewert, W. E. (Review of Economic Studies, 1980)
Journal Article Symmetry Conditions for Market Demand Functions Get access W. E. Diewert W. E. Diewert University of British Columbia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 3, April 1980, Pages 595–601, https://doi.org/10.2307/2297310 Published: 01 April 1980 Article history Received: 01 January 1977 Accepted: 01 August 1979 Published: 01 April 1980